Penerapan Model Pembelajaran Project Based Learning dalam Pembelajaran Mandiri pada Pendidikan Kesetaraan Paket C - Fauzi, Ahmad; Siregar, Herlina; Meilya, Ika Rizqi (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2019)
This study, the purpose of which the researchers want to point out is to find out the application of the projec based learning learning model in independent learning on package C equality education at PKBM Abdi Pertiwi Kec. Serant City Walantaka. The method used in this study is by using a descriptive qualitative approach. The technique of collecting data is by interview, observation and documentation. The results of the study show that the formulation of an effective learning model using the Project Based Learning (PjBL) strategy consists of the planning and implementation stages. The planning phase is the stage carried out by educators in designing independent learning with the PjBL strategy which consists of: 1) mapping of SK-KD; 2) determine the learning theme; 3) determine KD related to the theme; 4) develop indicators; 5) develop syllabus; and 6) developing RPP. The implementation stage is the stage of implementing the Project Based Learning steps in independent learning by students. This stage consists of steps: 1) asking; 2) plan the project; 3) make a schedule; 4) carry out the project; 5) monitoring; 6) assess; and 7) evaluate.